Three novel marine species of the genus Reichenbachiella exhibiting degradation of complex polysaccharides - Muhammad, Neak; Avila, Forbes; Nedashkovskaya, Olga I.; Kim, Song-Gun (Frontiers in Microbiology, 2023)
Three strains designated ABR2-5T, BKB1-1T, and WSW4-B4T belonging to the genus Reichenbachiella of the phylum Bacteroidota were isolated from algae and mud samples collected in the West Sea, Korea. All three strains were enriched for genes encoding up to 216 carbohydrate-active enzymes (CAZymes), which participate in the degradation of agar, alginate, carrageenan, laminarin, and starch. The 16S rRNA sequence similarities among the three novel isolates were 94.0-94.7%, and against all three existing species in the genus Reichenbachiella they were 93.6-97.2%. The genome sizes of the strains ABR2-5T, BKB1-1T, and WSW4-B4T were 5.5, 4.4, and 5.0 Mb, respectively, and the GC content ranged from 41.1-42.0%. The average nucleotide identity and the digital DNA-DNA hybridization values of each novel strain within the isolates and all existing species in the genus Reichenbachiella were in a range of 69.2-75.5% and 17.7-18.9%, respectively. The three strains exhibited a fatty acid profile characterized by elevated levels of iso-C15:0 (37.7-47.4%) and C16:1 ω5c (14.4-22.9%). Specifically, strain ABR2-5T displayed an higher proportion of C16:0 (13.0%). The major polar lipid was phosphatidylethanolamine, unidentified lipids, aminolipids, and glycolipids. Menaquinone-7 was identified as the respiratory quinone. A comparative genome analyses revealed that the isolates harbored many key genes involved in central metabolism for the synthesis of essential amino acids and vitamins, hydrolytic enzymes, carotenoid pigments, and antimicrobial compounds. The KEGG analysis showed that the three isolates possessed a complete pathway of dissimilatory nitrate reduction to ammonium, which is involved in the conservation of bioavailable nitrogen within the ecosystem. Moreover, all the strains possessed genes that participated in the metabolism of heavy metals, including arsenic, copper, cobalt, ferrous, and manganese. All isolates contain the class 2 type II subtype C1 CRISPR-Cas system in their genomes. The distinguished phenotypic, chemotaxonomic, and genomic characteristics led us to propose that the three strains represent three novel species in the genus Reichenbachiella: R. ulvae sp. nov. (ABR2-5 T = KCTC 82990 T = JCM 35839 T ), R. agarivorans sp. nov. (BKB1-1 T = KCTC 82964 T = JCM 35840 T ), and R. carrageenanivorans sp. nov. (WSW4-B4T = KCTC 82706T = JCM 35841T).